2013
DOI: 10.1002/anie.201307389
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Spin Isomers of Ethylene: Enrichment by Chemical Synthesis and Application for NMR Signal Enhancement

Abstract: Taking CH2CH2 for a spin: Enrichment of the nuclear spin isomers of ethylene was achieved by a catalytic reaction of acetylene with parahydrogen (see scheme). The spin isomers were used for NMR signal enhancement, both with and without subjecting them to a chemical reaction. The interconversion times of the nuclear spin isomers were evaluated at ambient pressure, thus revealing extremely long‐lived spin states with lifetimes of (1000±400) s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 44 publications
(43 reference statements)
3
65
2
1
Order By: Relevance
“…Another interesting substrate for heterogeneous hydrogenation with parahydrogen is acetylene. The product of this reaction is ethylene, which, in the case of a pairwise addition of pH 2 , is enriched with certain spin isomers . Such an enrichment cannot be detected by using NMR spectroscopy, owing to the magnetic equivalence of the hydrogen atoms in ethylene; however, if the magnetic equivalence is broken, direct NMR detection becomes possible.…”
Section: Heterogeneous Phipmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting substrate for heterogeneous hydrogenation with parahydrogen is acetylene. The product of this reaction is ethylene, which, in the case of a pairwise addition of pH 2 , is enriched with certain spin isomers . Such an enrichment cannot be detected by using NMR spectroscopy, owing to the magnetic equivalence of the hydrogen atoms in ethylene; however, if the magnetic equivalence is broken, direct NMR detection becomes possible.…”
Section: Heterogeneous Phipmentioning
confidence: 99%
“…The product of this reaction is ethylene, which, in the case of ap airwise addition of pH 2 ,i se nriched with certain spin isomers. [152] Such an enrichment cannotb ed etected by using NMR spectroscopy,o wing to the magnetic equivalence of the hydrogen atoms in ethylene;h owever,i ft he magnetic equivalence is broken, direct NMR detectionb ecomes possible. Zhivonitko et al showed that it was possible to obtain ah yperpolarized adduct with distinctive antiphase signals in the NMR spectra by adding perfluoro(para-tolylsulfenyl)chloride to ethylene, which was produced by the hydrogenation of acetylene with parahydrogen over aP d/TiO 2 catalyst.…”
Section: Heterogeneous Phipmentioning
confidence: 99%
“…15 min. [234] The further RD NMR development could concern utilization of such extremely long-lived HP. In addition, the progress achieved in the field of single-scan ultra-fast NMR techniques [235] also offers new capabilities, which earlier were considered incompatible with NMR hyperpolarization.…”
Section: Remote-detection Mri Of Hyperpolarized Gasesmentioning
confidence: 99%
“…15 min. [233] The further RD NMR development could concern utilization of such extremely longlived HP. In addition, the progress achieved in the field of singlescan ultra-fast NMR techniques [234] also offers new capabilities, which earlier were considered incompatible with NMR hyperpolarization.…”
Section: Outcome and Perspectivesmentioning
confidence: 99%